Rheological properties of mixtures of sugarcane bagasse and wheat bran during solid-state cultivation - Canedo, Marianny Silva [UNESP]; Figueiredo, Maria Fernanda Santos [UNESP]; Thoméo, João Cláudio [UNESP] (Springer Nature, 2021)
This work aimed to obtain rheological parameters of a medium composed by sugarcane bagasse and wheat bran before and during the cultivation with Myceliophthora thermophila I-1D3b. A texture profile analysis (TPA) was performed and assays of compression and tensile strength were carried out and the parameters such as hardness, cohesiveness and springiness were determined. For the experiments of tensile strength, the fungus was cultivated in two discs of wheat bran separated by a definite void, which was filled by the aerial mycelium along the cultivation and the force required to take apart both discs was measured as a function of the cultivation time. Another tensile strength experiment was carried out in a block of sugarcane bagasse and wheat bran and the force required to disrupt the block was measured along the cultivation. Experiments of double compression before the cultivation were carried out moistening the samples well in advance of the experiment (15 days) and just before the experiment. Experiments of double compression during the cultivation were done with samples at different moisture contents and cultivation times, moistening the samples just before the experiment. The results showed that moistening the samples well before the experiment produced harder samples. A trend of decrease of the compression force was noticed with the increase of the cultivation time, indicating physical degradation of the solid material. The maximum breaking stress of the hyphaes and of the cultivated medium took place at 24 h of cultivation, which was coincident with the maximum respirometric activity of the fungus. This work brings new methods of determination of mechanical properties to the solid-state cultivation field and the determined parameters will be of help for modeling particle movement during the cultivation in different types of bioreactors.
Keywords: Myceliophthora thermophila I-1D3b; Solid rheology; Solid-state cultivation; Sugarcane bagasse; Texture profile analysis